Exosomal-microRNAs Improve Islet Cell Survival and Function In Islet Transplantation - Minhua, Qiu; Bingzheng, Feng; Zhiran, Xu; Yingying, Zhang; Yuwei, Yang; Ting, Zhang; Jibing, Chen; Hongjun, Gao (Current Stem Cell Research & Therapy, 2024)
Exosomal-microRNAs (Exo-miRNAs) are key regulators of islet cell function, including insulin expression, processing, and secretion. Exo-miRNAs have a significant impact on the outcomes of islet transplantation as biomarkers for evaluating islet cell function and survival. Furthermore, they have been linked to vascular remodeling and immune regulation following islet transplantation. Mesenchymal stem cell-derived exosomes have been shown in preliminary studies to improve islet cell viability and function when injected or transplanted into mice. Overall, Exo-miRNAs have emerged as novel agents for improving islet transplantation success rates. The role of islet-derived Exo-miRNAs and mesenchymal stem cells-derived Exo-miRNAs as biomarkers and immunomodulators in islet regeneration, as well as their role in improving islet cell viability and function in islet transplantation, are discussed in this review.
Keywords: antiapoptosis